Different efficiency of auxiliary/chaperone proteins to promote the functional reconstitution of honeybee glutamate and acetylcholine receptors in Xenopus laevis oocytes. Issue 5 (3rd June 2022) - Brunello, Lorène; Ménard, Claudine; Rousset, Matthieu; Vignes, Michel; Charnet, Pierre; Cens, Thierry
Abstract: Heterologous expression systems (e.g., Xenopus laevis oocytes) are useful to study the biophysical properties and pharmacology of ionotropic receptors such as ionotropic glutamate (iGLuRs) and nicotinic acetylcholine (nAChRs) receptors. However, insect receptors often require the co‐expression of chaperone proteins to be functional. Only few iGluRs and nAChRs have been successfully expressed in such systems. Here, we compared the efficiency of chaperone proteins to promote the functional expression of one Apis mellifera iGluR and several nAChR subunit combinations (α1α8β1, α7, α2α8β1 and α2α7α8β1) in Xenopus oocytes. To this end, we cloned a new iGluR (GluR‐1) and potential chaperone proteins (e.g., SOL‐1, Neto, NACHO) and tested more than 40 combinations of human, nematode and honeybee proteins. We obtained robust expression of GluR‐1 and α1α8β1 when co‐expressed with honeybee chaperone proteins and found that nAChR expression critically depended on the α1 subunit N‐terminal sequence. We recorded small ACh‐gated currents in few oocytes when the α7 subunit was co‐expressed with Caenorhabditis elegans RIC‐3, but none of the chaperone proteins allowed efficient expression of α2α8β1 or α2α7α8β1. Our results show that only some protein combinations can reconstitute functional receptors in Xenopus oocytes and that protein combination efficient in one species is not always efficient in another species. Abstract : Insect ionotropic receptors are difficult to express in heterologous system. Honeybee GluR‐1 is functional when co‐expressed with honeybee chaperone proteins but not α7, α2α8β1 and α2α7α8β1 nAChRs. Expression of α1‐containing nAChRs critically depends on α1 N terminus.